2017
DOI: 10.1098/rsbl.2017.0445
|View full text |Cite
|
Sign up to set email alerts
|

The loneliness of the long-distance toad: invasion history and social attraction in cane toads ( Rhinella marina )

Abstract: Individuals at the leading edge of a biological invasion constantly encounter novel environments. These pioneers may benefit from increased social attraction, because low population densities reduce competition and risks of pathogen transfer, and increase benefits of information transfer. In standardized trials, cane toads () from invasion-front populations approached conspecifics more often, and spent more time close to them, than did conspecifics from high-density, long-colonized populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…We chose these assays to look for differences between de-toxined versus control toads because previous studies indicate they are effective tools to measure differences among groups of toads (e.g. as a function of infection status [37], invasion history [27,39] or immune response [40]).…”
Section: (Ii) Captive Toadsmentioning
confidence: 99%
“…We chose these assays to look for differences between de-toxined versus control toads because previous studies indicate they are effective tools to measure differences among groups of toads (e.g. as a function of infection status [37], invasion history [27,39] or immune response [40]).…”
Section: (Ii) Captive Toadsmentioning
confidence: 99%
“…Assortative mating has favoured long-range dispersers at the invasion front [60], but this in turn generates low-density populations and conditions of relative social isolation in newlyfounded habitats [61]. A study examining the effect of these factors used toads from a recentlycolonized (< 3 years) population in Western Australia to compare with toads from populations that had been evolving under relatively constant, high densities for approximately 80 years in eastern Australia and Hawaii [62]. Social attraction differed among the populations in a manner consistent with selection imposed by social isolation at the invasion front: toads of both sexes from the newlyestablished population in Western Australia were more likely to approach a social partner and spend more time with that individual.…”
Section: Evidence That Social Isolation Impacts Evolutionmentioning
confidence: 99%
“…It can also function as an anti-predatory strategy through the effects of predator dilution and group vigilance (Lanham & Bull, 2004;Pizzatto et al, 2016). What's more, conspecific aggregation may also have the benefit of enhanced resource acquisition and thermoregulation (Stamps, 1988;Gruber et al, 2017). Individuals may be attracted to the presence of conspecifics as they can serve as cues to the location of food and quality habitat as well as mitigate physiological stressors imposed by the abiotic environment (Khan, Richardson & Tattersall, 2010;Pizzatto et al, 2016;Gruber et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yet research exploring conspecific attraction between populations is lacking. It has been suggested that signal divergence may be driven by local adaptation to varying selective regimes (Seddon, 2005;Gruber et al, 2017). Variation in the signalling environment could result in morphological and/or behavioural differentiation among populations which serve as visual cues during the recognition process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation